ANALISIS PERBANDINGAN KINERJA KEUANGAN PEMERINTAH KABUPATEN / KOTA KAWASAN METROPOLITAN MEBIDANGRO TAHUN ANGGARAN 2011-2014 - Putri, Moulisa Friana; Islahuddin, Islahuddin (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2018)
Performance is an overview of actifity implementation achieved level or program or wisdom in give shape to getting goal, direction, mission, and vision of organization as started in strategic planning in it. Analysis of monetary performances is important to evaluate the success about local government financial management. This research aimed to combare the monetary performance between in regency district and city in Metropolitan Mebidangro. This research is quantitative descriptive reaserch. Collection data technique that used in this research using documentation technique. The data used are secondary data from the regional budget report and realization reports revenue expenditure fiscal year 2011-2014. To measure performace using difference analysis tool that analyses the budget and analysis of finantial ratio such as analysis of budget variance, analysis of financial independency, fiscal decentralization, effectiveness, growth, and harmony. The results showed the government's performance is better than the Karo district / city government more views from both the budget difference analysis of variance of revenue and expenditure variance. For the level of independence and the degree of fiscal decentralization Medan city government is superior compared with the district / city. To rate the effectiveness of PAD, the government Karo considered better than with the district / city. From the ratio of revenue growth and spending, government Binjai show higher growth while revenue growth, Medan showed higher growth compared with the district / city. For compatibility ratio shows Deli Serdang district governments have higher operating expenditures, while for the highest level of capital expenditure is at Binjai government